2019
DOI: 10.1088/1361-6463/ab01ee
|View full text |Cite
|
Sign up to set email alerts
|

Double in-plane-gate IZO-based thin-film transistors with pea protein gate dielectrics

Abstract: Double in-plane-gate indium-zinc-oxide (IZO) thin-film transistors (TFTs) using pea protein as the gate dielectric films were fabricated on ITO glass substrates at room temperature. Pea protein, a natural biodegradable solid electrolyte, showed a very high specific gate capacitance of 2.0 μF cm −2 at 1.0 Hz due to the electric-double-layer effect. The field effect mobility, current ON/OFF ratio, and subthreshold swing of the IZO-based TFTs with bottom gate were estimated to be 27.6 cm 2 V −1 s −1 , 3 × 10 6 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Especially due to the relatively low capacity of portable battery, logic circuits with low power consumptions are extremely desirable. As indicated previously, electrolyte gated oxide transistors provide promising strategies for decreasing power consumption, as is meaningful for logic circuits with low-power consumption [22][23][24]. Herein, low-voltage PVA/GO hybrid electrolyte gated ITO based oxide neuron transistors were fabricated.…”
Section: Introductionmentioning
confidence: 92%
“…Especially due to the relatively low capacity of portable battery, logic circuits with low power consumptions are extremely desirable. As indicated previously, electrolyte gated oxide transistors provide promising strategies for decreasing power consumption, as is meaningful for logic circuits with low-power consumption [22][23][24]. Herein, low-voltage PVA/GO hybrid electrolyte gated ITO based oxide neuron transistors were fabricated.…”
Section: Introductionmentioning
confidence: 92%
“…[10][11][12][13] Indium oxide (In 2 O 3 ) is a wide bandgap (3.75 eV) semiconductor material with high electron mobility (theoretical value ∼ 270 cm 2 •V −1 •s −1 ) and high transparency, and it has been widely used in semiconductor optoelectronic devices. [14][15][16] Recently, efforts have been made to improve its properties by doping elements such as Sn, [17] Mo, [18] Ga, [19] Zn, [20] and so on. Among them, W-doped In 2 O 3 (IWO) have recently gained interest following the experimental demonstration of IWO field effect transistors with ultra-high on/off current ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that the area of the gate electrode scales with the channel current [21]. IPGTs are generally based on metal oxides semiconductors or heterostructures of gallium or indium, manufactured using photolithography and vacuum deposition techniques, as radiofrequency magnetron sputtering [15,16,[20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%